2015
DOI: 10.1021/acs.iecr.5b01775
|View full text |Cite
|
Sign up to set email alerts
|

Application of Microimpinging Stream Reactors in the Preparation of CuO/ZnO/Al2O3 Catalysts for Methanol Synthesis

Abstract: A microimpinging stream reactor (MISR) at the size of 1 mm was built with a commercial T-junction and steel capillaries for the preparation of CuO/ZnO/Al 2 O 3 catalysts. The coprecipitation of catalyst precursors in MISR was conducted under precisely controlled concentration, pH and volumetric flow rate (V A ), followed by the conventional postprecipitation steps. TEM images showed that the coprecipitation in MISR would generate mostly round catalyst particles with a mean size of 8−10 nm; whereas slightly lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…A micro-impinging stream reactor (MISR) was built and applied to prepare CuO/ZnO/Al 2 O 3 catalysts for methanol synthesis in our previous studies. 28,29 The MISR is constructed with two steel capillaries connected to a commercial T-junction, but no tube is connected to the T-junction outlet, which provides a big-sized channel to lead the reacted precipitates into sample collectors for the next step. The two streams impinge on each other directly inside the T-junction to create a quick and constant supersaturation level and therefore a more homogeneous nucleation environment for the quick precipitating process, which may have been completed within the T-junction chamber.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A micro-impinging stream reactor (MISR) was built and applied to prepare CuO/ZnO/Al 2 O 3 catalysts for methanol synthesis in our previous studies. 28,29 The MISR is constructed with two steel capillaries connected to a commercial T-junction, but no tube is connected to the T-junction outlet, which provides a big-sized channel to lead the reacted precipitates into sample collectors for the next step. The two streams impinge on each other directly inside the T-junction to create a quick and constant supersaturation level and therefore a more homogeneous nucleation environment for the quick precipitating process, which may have been completed within the T-junction chamber.…”
Section: Introductionmentioning
confidence: 99%
“…In previous work, CuO/ZnO/Al 2 O 3 catalysts have been prepared in MISR with better microstructures and properties as well as higher catalytic activity in methanol synthesis than those prepared in STR, 29 as a result of the intensied micromixing within the MISR reactor for the precipitating process as well as a more uniform and steady environment for the subsequent aging process. In this work, we combined fast precipitation and freeze-drying to investigate the phase transitions during the rst seconds of the precipitation, and then provided a detailed study on the effects of post-precipitation processes on the properties and activity of CuO/ZnO/Al 2 O 3 catalysts and their precursors produced in MISR and traditional STR, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8] The most prominent catalytic system for industrial methanol synthesis since decades ago is based on Cu/ZnO/(Al 2 O 3 ) and enormous efforts have been dedicated to the enhancement of its catalytic activity based on rational design via different preparation methods. 3,5,[9][10][11][12][13][14][15][16][17][18][19] One widely applied method for the synthesis of Cu/ZnO/(Al 2 O 3 ) is coprecipitation of soluble copper, zinc and aluminum precursors using e.g. sodium carbonate.…”
Section: Introductionmentioning
confidence: 99%
“…Their catalytic activity depends on such factors as their components, active surface area, and CuO and ZnO distribution. Among these influence factors, the distribution of CuO and ZnO has been proven to be one of the most important factors, which is mainly controlled during the aging step. During the aging process, the mutual substitution between Cu 2+ in malachite (Cu 2 CO 3 (OH) 2 ) and Zn 2+ in hydrozincite (Zn 5 (OH) 6 (CO 3 ) 2 ) occurs in the mother liquor, resulting in the formation of Cu/Zn hydroxy carbonate precursors, i.e., zincian malachite ((Cu,Zn) 2 CO 3 (OH) 2 ) and/or aurichalcite ((Cu,Zn) 5 (OH) 6 (CO 3 ) 2 ), which leads to an outstanding catalytic activity after calcination. However, this ion exchange between Cu 2+ and Zn 2+ to form Cu/Zn hydroxy carbonate precursors is very susceptible to the aging conditions, such as the pH value of mother liquor, aging temperature, aging duration, and stirring velocity. ,, For example, Farahani et al reported that, at a constant aging time of 5 h, the catalytic activity of a prepared Cu–Zn catalyst for methanol synthesis first increases, passes through a maximum, and then decreases with increasing aging temperature from 40 to 80 °C, and the highest activity was obtained at 60 °C.…”
Section: Introductionmentioning
confidence: 99%
“…During the aging process, the mutual substitution between Cu 2+ in malachite (Cu 2 CO 3 (OH) 2 ) and Zn 2+ in hydrozincite (Zn 5 (OH) 6 (CO 3 ) 2 ) occurs in the mother liquor, resulting in the formation of Cu/Zn hydroxy carbonate precursors, i.e., zincian malachite ((Cu,Zn) 2 CO 3 (OH) 2 ) and/or aurichalcite ((Cu,Zn) 5 (OH) 6 (CO 3 ) 2 ), which leads to an outstanding catalytic activity after calcination. However, this ion exchange between Cu 2+ and Zn 2+ to form Cu/Zn hydroxy carbonate precursors is very susceptible to the aging conditions, such as the pH value of mother liquor, aging temperature, aging duration, and stirring velocity. ,, For example, Farahani et al reported that, at a constant aging time of 5 h, the catalytic activity of a prepared Cu–Zn catalyst for methanol synthesis first increases, passes through a maximum, and then decreases with increasing aging temperature from 40 to 80 °C, and the highest activity was obtained at 60 °C. In addition, the fact that the Cu/Zn hydroxy carbonate precursors were obtained from the solid phase of the raw material, dissolved to the liquid state, and then recrystallized to solid state via tedious multistep processing is very inconvenient and uneconomical.…”
Section: Introductionmentioning
confidence: 99%